Posttraumatic stress disorder and posttraumatic growth in HIV-infected patients – the role of coping strategies - Nina Ogińska-Bulik; Klaudia Kraska (Health Psychology Report, 2017)
Background The purpose of the research was to establish the role of coping strategies in the occurrence of posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG) in HIV-infected individuals.